284 IMPACT OF THE DIETARY SUPPLEMENT HEALTH AND EDUCATION ACT OF 1994 ON MAGAZINE ADVERTISING AND SALES OF WEIGHT LOSS AND DIETARY SUPPLEMENTS. (1st January 2005) - Kennedy-Darling, J.; Ferris, N.; Kuehl, K.; Elliot, D.
Abstract : Purpose: Magazine advertising has been associated with influencing body image and dietary behaviors. Since enactment of Dietary Supplement Health and Education Act (DSHEA) ten years ago, dietary supplements of unproven value have been advertised with false and misleading claims, and some causing serious health risks. There are no studies linking magazine advertising to increased weight loss and dietary supplement (WL&DS) use. Our purpose was to compare the number of pages of WL&DS advertisements in popular magazines prior to, and ten years after passage of DSHEA, and compare this to retail sales of supplements during the same time period. Methods: We selected a convenience sample of 10 major national magazines during 1993-1994 from local libraries counting the pages of WL&DS ads comparing this to the pages of WL&DS ads during 2003-2004. Overall, 431 issues among the 10 magazines were assessed for ads prior to (1993-94) and ten years after (2003-04) passage of DSHEA. Retail sales of weight loss and dietary supplements were assessed for the same time period prior to and ten years after DSHEA. Results: Mean WL advertisements increased from 1.3 pages per issue prior to DSHEA to a mean of 2.8 (115%) pages per issue after DSHEA, despite no change in total number of pages of magazines per issue. Mean DS advertisements increased from 0.9 pages per issue prior to DSHEA to a mean of 5.6 (607%) pages per issue after DSHEA, with no change in the total number of pages per issue. At the same time, retail sales of WL&DS increased from 4.8 billion dollars in 1993 to 39 billion dollars in 2003. Conclusion: Since DSHEA, a dramatic increase in magazine advertising and sales of unregulated weight loss and dietary supplements have occurred. There is cause for concern about the volume and variety of supplement advertising as well as the false and misleading claims regarding potentially harmful substances.